Case study on analyses of slope riverbank failure - Nazaruddin Abdul Taha; Mohamad Shakri Mohmad Shariff; Mohd Azizul Ladin (John Wiley & Sons, 2022)
A slope riverbank failure is a natural event that occurs globally on each riverbank, and a drawdown event usually causes slope riverbank failure. This case study is aimed at analysing slope riverbank failures by evaluating the seepage and slope stability of the riverbank under slow and rapid drawdown. The riverbank in this case study is located at KM 3.49, Jalan Pantai Luagan in the Sipitang district (N 4° 59′ 12.9″ E 115° 31′ 13.3″). A literature review was conducted to view the current study pattern and retrieve a methodology based on the current study pattern. GeoStudio is a commercial finite element software. The data obtained from the borehole log report and online resources were utilised to create the riverbank model in software. The phreatic line shows a slow change over time, indicating that the riverbank takes a long time to stabilise after the drawdown. The FOS value decreases during the drawdown occurrence and slowly increases after the drawdown has ended. In conclusion, the drawdown event can cause slope riverbank failure, and the seepage and stability analysis using GeoStudio can show the condition of the riverbank during the drawdown event.